PENERAPAN TRI HITA KARANA PADA MANAJEMEN SATRIA AGROWISATA DI KECAMATAN TAMPAKSIRING, KABUPATEN GIANYAR - Padmidewi, Desak Putu; Windia, Wayan -; Sudarma, I Made (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 7 No 1 (2019): MEI 2019DO - 10.24843/JMA.2019.v07.i01.p2, 2019)
ABSTRACT Tri Hita Karana has becomes the foundation of development in the Province of Bali, its reflected in the vision of the development in the Province of Bali in 2006-2026 "Bali Dwipa Jaya, Fair, and Democratic, and Safe and Unified". Tri Hita Karana has becomes the foundation of development in Bali, the Tri Hita Karana must be applied to various community activities such as politics, economics, socials, defenses, and securities. Satria Agrowisata has application the Tri Hita Karana concept. The research aimed to analyzed the suitability between expectations and realities on the application of Tri Hita Karana at Satria Agrowisata, to analyzed the connection of application of Tri Hita Karana with management of Satria Agrowisata, and to analyzed satisfied visitors of Satria Agrowisata toward agrotourism activities with Tri Hita Karana application. Data of  this research were used qualitative and quantitative. The research location is in Satria Agrowisata was chosen by purposive. The researchs were used two types of sampling methode such as census sampling and accidental sampling. Collection of data in the research were used several methods such as observations, interviews, and documentations. To analyzed the data, the research were used descriptive qualitative analysis method and Rank Spearman correlation. The results of the researchs were show the suitability between expectations and realities on the application of Tri Hita Karana at Satria Agrowisata is very suitable. The connection between Tri Hita Karana and management in agrotourism is very weak. Visitors of Satria Agrowisata were very satisfied with agrotourism activities in Satria Agrowisata which Tri Hita Karana application. The suggestions are to continue the application of Tri Hita Karana in activities agrotourism, to improve the connection between the application of Tri Hita Karana and management at the Agrotourism, and Satria Agrowisata needs to improve the quality of their service and add varieties of drinks and foods.